2022
DOI: 10.3389/fcell.2022.824165
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Pathways of Pyroptosis in Atherosclerosis

Abstract: Atherosclerosis (AS) is a chronic inflammatory disease seriously endangering human health, whose occurrence and development is related to many factors. Pyroptosis is a recently identified novel programmed cell death associated with an inflammatory response and involved in the formation and progression of AS by activating different signaling pathways. Protein modifications of the sirtuin family and microRNAs (miRNAs) can directly or indirectly affect pyroptosis-related molecules. It is important to link atheros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 124 publications
0
10
0
Order By: Relevance
“…However, pyroptosis may also be detrimental to the body, now that the deterioration of diseases occurs with pyroptosis. It is reported that pyroptosis plays an essential role in several diseases, such as cancers, atherosclerosis, and so on [ 57 , 65 , 79 ]. Respiratory diseases are considered to account for the increased mortality rate [ 64 , 67 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, pyroptosis may also be detrimental to the body, now that the deterioration of diseases occurs with pyroptosis. It is reported that pyroptosis plays an essential role in several diseases, such as cancers, atherosclerosis, and so on [ 57 , 65 , 79 ]. Respiratory diseases are considered to account for the increased mortality rate [ 64 , 67 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that respiratory diseases are closely related to inflammation [ 30 , 48 ]. Increasing evidence indicates that pyroptosis is crucial for inflammatory diseases [ 65 ]. Recently, accumulative studies focus on the role of pyroptosis in the inflammatory diseases of the lung [ 89 , 91 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pyroptosis can cause inflammation that is activated by extracellular or intracellular stimuli [ 52 ] and is associated with various diseases, such as cardiovascular disease [ 53 ], Alzheimer’s disease [ 54 ], atherosclerosis [ 55 ], and muscle atrophy [ 56 ]. A recent study showed that pyroptosis occurs during dexamethasone-induced muscle atrophy [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…The known signaling pathways of pyroptosis on atherosclerosis are nuclear factors such as NF-κB, AMPK, MAPK, SIRT, as well as miRNA, which may shed light on therapeutic targets for the treatment of atherosclerosis [ 111 ]. The vital role of pyroptosis in the pathogenesis of atherosclerosis has generated a few specific inhibitors or agents that target bioactive substances such as NLRP3, caspase-1, caspase-4/5/11, GSDMD, and other candidates in relation to pyroptosis pathway [ 7 ][ 81 ][ 84 ].…”
Section: Mediation and Therapeutic Targets Of Pyroptosis In Nlrp3 Inf...mentioning
confidence: 99%